Test–Retest Reliability of Remote ImPACT Administration. (16th July 2021) - Netzel, Lauren; Moran, Ryan; Hopfe, Dustin; Salvatore, Anthony P; Brown, Warren; Murray, Nicholas G
Abstract: Objective: To evaluate the performance and test–retest reliability obtained when administering a computerized baseline neurocognitive exam to NCAA Division I student-athletes in a controlled laboratory setting versus an uncontrolled remote location. Method: A sample of 129 (female = 100) Division I student-athletes completed Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) pre-season assessments for two distinct and respective sports seasons in a controlled laboratory environment and an uncontrolled remote environment. Depending on the environment, participants were given verbal (controlled) or written (uncontrolled) guidelines for taking the test. Results: Multivariate repeated-measures ANOVA's determined that there were no within-subject differences between testing environments on ImPACT composite scores and cognitive efficiency index (CEI). The Chi-square test did not find any significant differences in impulse control or the number of invalid test scores, as determined by ImPACT, between environments. Intraclass correlations found the ImPACT subtest scores to range in test–retest reliability across testing environments, demonstrating moderate (verbal memory composite, r  = 0.46; visual memory composite, r  = 0.64; reaction time, r  = 0.61; impulse control, r  = 0.52; and CEI, r  = 0.61) and good (visual motor composite, r  = 0.77) test–retest reliability. Conclusions: Results indicate that ImPACT is reliable between controlled and uncontrolled testing environments. This further suggests that ImPACT can be administered in a remote environment, pending specific adherence to testing instructions, or in the event of social distancing or isolation policies.